Organic food and the impact on human health. Issue 4 (21st February 2019) - Hurtado-Barroso, Sara; Tresserra-Rimbau, Anna; Vallverdú-Queralt, Anna; Lamuela-Raventós, Rosa María
ABSTRACT: In the last decade, the production and consumption of organic food have increased steadily worldwide, despite the lower productivity of organic crops. Indeed, the population attributes healthier properties to organic food. Although scientific evidence is still scarce, organic agriculture seems to contribute to maintaining an optimal health status and decreases the risk of developing chronic diseases. This may be due to the higher content of bioactive compounds and lower content of unhealthy substances such as cadmium and synthetic fertilizers and pesticides in organic foods of plant origin compared to conventional agricultural products. Thus, large long-term intervention studies are needed to determine whether an organic diet is healthier than a diet including conventionally grown food products. This review provides an update of the present knowledge of the impact of an organic versus a conventional food diet on health.